Effects of buprenorphine and fentanyl in brachial plexus block on operative and post-operative analgesia: a clinical comparative study - Kumar Saharia, Hiranya; Devi, Rajita (International Journal of Medical Research and Review, 2016)
Introduction: Surgical pain is an acute pain and is defined as conscious perception of noxious stimuli. Peripheral neural blockade has brought a new dimension in regional anaesthesia and is now a well accepted component of comprehensive anaesthetic technique. Aim: The study aimed to compare the quality of intra-operative analgesia and the duration of post-operative analgesia with use of buprenorphine and fentanyl administered with lignocaine with adrenaline in the brachial plexus block through the catheter technique of axillary brachial plexus blockade for upper limb surgeries. Materials and Methods: The study included 30 patients in group A (buprenorphine) and 30 in group B (fentanyl) with ASA I and ASA II physical status of either sex, in the age group of 15 to 60 years weighing between 45 to 85 kg undergoing upper limb surgeries. Results: The onset of analgesia in the operative and post operative doses was earlier with fentanyl than buprenorphine. The duration of analgesia in operative dose and post operative doses was more with buprenorphine. Quality of analgesia is found to be better with fentanyl. Conclusion: patients suffer needlessly due to improper post operative analgesia. So, the results of this study can be incorporated in anesthetic technique to reduce patient’s post operative pain.